2009
DOI: 10.1038/aps.2009.107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MMP-3 activity and invasion of the MDA-MB-231 human invasive breast carcinoma cell line by bioflavonoids

Abstract: IntroductionMetastatic invasion is the primary cause of patient mortality during breast cancer progression. For a transformed cell to metastasize to a distant site in the body, it must first lose adhesion, penetrate and invade the surrounding extracellular matrix (ECM), enter the vascular system, and adhere to distant organs [1] . The inhibition of invasion of cancer cells has been an important strategy in cancer treatment [2] . A crucial step in the invasive processes is the proteolytic degradation of the ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 41 publications
2
41
0
3
Order By: Relevance
“…We also investigated the suppressive mechanisms of MMP-1 down-regulation by naturally-occurring flavonoids in human dermal fibroblasts (14). Recently, it was also found that quercetin and kaempferol reduced MMP-3 activity in breast carcinoma cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the suppressive mechanisms of MMP-1 down-regulation by naturally-occurring flavonoids in human dermal fibroblasts (14). Recently, it was also found that quercetin and kaempferol reduced MMP-3 activity in breast carcinoma cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…Some flavonols have been reported to control the function of specific MMPs by inhibiting their catalytic activity (Phromnoi et al, 2009;Sartor et al, 2002). Recently, we also found that one flavonol, fisetin, inhibits the catalytic activity of various MMPs, including MMP-14, and reduces MMP-dependent cellular processes, such as tumor cell invasion and endothelial cell tube formation .…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have suggested that the aqueous extract of amla was effective in preventing the invasion of MDAMB-231 cells in the in vitro matrigel invasion assay [38]. The amla phytochemical, kaempferol, inhibited the expression of stromelysin1 (MMP-3) in the MDA-MB-231 breast cancer cell line [39]. The polyphenol gallic acid is also reported to possess inhibitory effects on gastric adenocarcinoma cell migration, decreased expression of MMP-2/9 in vitro [40], It has been shown to exhibit a variety of biological activities including ant-oxidative activity [41].…”
Section: Discussionmentioning
confidence: 99%